2020
DOI: 10.1017/jfm.2019.1047
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability of katabatic Prandtl slope flows with ambient wind forcing

Abstract: We investigate the stability of katabatic slope flows over an infinitely wide and uniformly cooled planar surface subject to an additional forcing due to a uniform downslope wind field aloft. We adopt an extension of Prandtl's original model for slope flows (Lykosov & Gutman 1972) to derive the base flow, which constitutes an interesting basic state in stability analysis because it cannot be reduced to a single universal form independent of external parameters. We apply a linear modal analysis to this basic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Numerical simulations are performed by solving the incompressible form of the buoyancy‐driven Navier–Stokes equations under the Boussinesq approximation. Specifically, we use a second‐order accurate finite‐difference solver Jacobsen and Senocak (2013) that was also adopted in the works of Xiao and Senocak (2019, 2020a, 2020b); Senocak and Xiao (2020). We apply the same grid resolution and boundary conditions as used by Xiao and Senocak to investigate the instabilities of the primary modes further for multiple slope flow configurations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical simulations are performed by solving the incompressible form of the buoyancy‐driven Navier–Stokes equations under the Boussinesq approximation. Specifically, we use a second‐order accurate finite‐difference solver Jacobsen and Senocak (2013) that was also adopted in the works of Xiao and Senocak (2019, 2020a, 2020b); Senocak and Xiao (2020). We apply the same grid resolution and boundary conditions as used by Xiao and Senocak to investigate the instabilities of the primary modes further for multiple slope flow configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Local linear stability analysis has been used to study the propagation of infinitesimal disturbances to Prandtl's laminar solution for slope flows. Such studies reported in the literature have revealed the existance of two distinct types of primary instabilities for katabatic as well as anabatic Prandtl slope flows, with Xiao and Senocak (2020a) and without ambient winds aloft Senocak (2019, 2020b); Senocak and Xiao (2020). These modes of instability are denoted as transverse and longitudinal.…”
Section: Flow Instabilities Of Prandtl Slope Flowsmentioning
confidence: 90%
See 1 more Smart Citation
“…In recent studies, we have investigated the linear stability of the Prandtl model for katabatic (Xiao & Senocak 2019) and anabatic (Xiao & Senocak 2020 b ) slope flows, as well as the extended version of the Prandtl model with ambient winds (Xiao & Senocak 2020 a ), and discovered the existence of a stationary roll instability at small slope angles, and a travelling wave instability at steeper slopes. These studies have also helped to establish the importance of the dimensionless stratification perturbation parameter in controlling the dynamics of stably stratified slope flows.…”
Section: Introductionmentioning
confidence: 99%